2021
DOI: 10.12688/wellcomeopenres.16412.1
|View full text |Cite
|
Sign up to set email alerts
|

Patient pathways for cardiovascular diseases in Malaysia and the Philippines: a systematic review

Abstract: Background: Cardiovascular diseases (CVDs) are the leading cause of premature mortality in the world and are a growing public health concern in low- and middle-income countries (LMICs), including those in South East Asia. Their management requires coordinated responses by a range of healthcare providers, which should preferably be based on knowledge of the national context. We systematically review evidence on the pathways followed by patients with CVD in Malaysia and the Philippines to understand patient jour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…28 Previously conducted health system appraisals involving communities from Colombia and Malaysia revealed that individuals with diagnosed hypertension may refrain from initiating antihypertensive medications for fear of adverse side effects or may stop their medications once symptoms appear to subside. 20,29 Such misperceptions may be perpetuated by family members, 30 and thus proper education is vital when considering their role as treatment supporters. The need for education and role-specific guidance for family members was recognized by Shen et al 24 as their intervention offered training sessions for supporters and patients.…”
Section: Discussionmentioning
confidence: 99%
“…28 Previously conducted health system appraisals involving communities from Colombia and Malaysia revealed that individuals with diagnosed hypertension may refrain from initiating antihypertensive medications for fear of adverse side effects or may stop their medications once symptoms appear to subside. 20,29 Such misperceptions may be perpetuated by family members, 30 and thus proper education is vital when considering their role as treatment supporters. The need for education and role-specific guidance for family members was recognized by Shen et al 24 as their intervention offered training sessions for supporters and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is possible to achieve good control in LMICs. A recent review of patient pathways for CVDs in Malaysia and the Philippines identified some examples of effective long-term management and control ( Seguin et al., 2021 ). To achieve control, it is necessary to understand the diverse pathways that patients follow, particularly regarding adherence to HT medication.…”
Section: Introductionmentioning
confidence: 99%